2006
DOI: 10.1021/ja062636h
|View full text |Cite
|
Sign up to set email alerts
|

Tautomerism in the Guanyl Radical

Abstract: Despite a few decades of intense study, a full description of tautomers of one-electron-oxidized guanine remains to be achieved. Here we show that two of these tautomers are produced by the protonation of an 8-haloguanine electron adduct. The rate constants for the reactions of hydrated electrons (eaq -) with a variety of 8-substituted guanine derivatives have been measured by a pulse radiolysis technique and correlated with both inductive and resonance components of the substituents. The fate of electron addu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
128
0
2

Year Published

2006
2006
2012
2012

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 79 publications
(135 citation statements)
references
References 56 publications
5
128
0
2
Order By: Relevance
“…These values are very similar to the analogous reactions with 8-bromoadenine [2,3] and 8-bromoguanine [4,6] nucleosides. The reaction of an aqueous solution of 8 (1 mm) and tBuOH (0.25 m) at pH% 7 with e aq À in the absence of O 2 was complete within % 300 ns.…”
supporting
confidence: 80%
See 2 more Smart Citations
“…These values are very similar to the analogous reactions with 8-bromoadenine [2,3] and 8-bromoguanine [4,6] nucleosides. The reaction of an aqueous solution of 8 (1 mm) and tBuOH (0.25 m) at pH% 7 with e aq À in the absence of O 2 was complete within % 300 ns.…”
supporting
confidence: 80%
“…The reactions of hydrated electrons (e aq À ) with 8-bromoadenine [1][2][3] and 8-bromoguanine nucleosides [4][5][6] have recently been investigated by radiolytic methods. It was found that 8-bromo-2'-deA C H T U N G T R E N N U N G oxyA C H T U N G T R E N N U N G adenosine (1) captures electrons and rapidly loses a bromide ion to give the corresponding C8 radical 2.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…þ . These questions have been treated by a number of authors employing both theory and experiment [142][143][144][145][146][147][148][149][150][151][152][153][154][155][156][157][158] without definitive conclusions. Recently, electron spin resonance (ESR) and the B3LYP/6-31G(d) level of theory have been used to identify the preferred site of deprotonation from guanine radical cation (G .…”
Section: -144mentioning
confidence: 99%
“…Similar conclusions were also drawn by Naumov and Sonntag 158 using UV-visible spectral properties and DFT study recently. Chatgilialoglu et al 155,156 also studied the tautomers of one-electron-oxidized guanosine using UV-visible spectral properties and the DFT method. Based on DFT results, they proposed the presence of a transient species G (N2-H) .…”
Section: Interestingly G(n1-h)mentioning
confidence: 99%